Pengaruh Perputaran Persediaan, Likuiditas dan Profitabilitas Terhadap Kualitas Laba Pada Perusahaan Food and Beverage Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Sri Rejeki; Dewi Saptantinah Puji Astuti (Akuntansi, 2024)
The aim of this research is to determine the significance of the influence of inventory turnover, liquidity and profitability on earnings quality in food and beverage sub sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research uses quantitative data, secondary data sources are company financial report. The number of samples in this research is 21 companies, sampling uses a purposive sampling method. The data collection method used is documentation methods, obtained from the official website www.idx.co.id and the official website of the food and beverage sub-sector company. The data analysis technique used is multiple linear regression analysis. The result of the t test study state that inventory turnover and liquidity has no significant effect on earnings quality in food and beverage sub sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period, while profitability has a significant negative effect on earnings quality in food and beverage sub sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research only uses food and beverage sub-sector companies as the object and uses three variables. Future researchers are expected to expand the research object and add other variables such as currency exchange rates, shipping costs, profit growth, accounts receivable turnover.